Retrospective study of disease incidence and other clinical conditions diagnosed in owned dogs in Delta State, Nigeria (Journal of Advanced Veterinary and Animal Research, 2015)
In  Nigeria,  knowledge  on  the  epidemiology  of diseases  of  dogs  is  limited.  A  retrospective  study  of data from clinical records of six veterinary clinics was undertaken  to  determine the  incidence  of  disease in owned dogs in Delta State, Nigeria from 2012 to 2014. Association between the diagnosed diseases and the studied  variables  was  explored  using  Chi-Squared test  statistics.  This  study  revealed  that  most  of  the conditions  presented  to  the  veterinary  clinics  were preventable.  Thirty-one  (31)  clinical  conditions  were diagnosed  from  571  cases  recorded,  involving nonspecific  (21.6%),  infectious  (70.9%;  P=0.001)  and non-infectious  (7.5%)  diseases.  The  most  occurring clinical  conditions  comprised  helminthoses  (21.4%), mange (10.5%), parvovirosis (8.4%), babesiosis (7.9%), septicemia  (7.2%),  gastroenteritis  (7.0%),  myiasis (7.0%),  trauma  (6.3%),  poisoning  (6.0%), ectoparasitism  (3.7%),  ascites  (2.5%),  dermatitis (2.3%),  aural  hematoma  (1.2%),  and  orchitis  (1.1%). Disease  incidence  was  highest  in  Alsatian  (40.3%), mixed/cross (33.1%), Rottweiler (7.0%) and toy breeds (4.6%). Details on the least occurring diseases and the association between disease and the studied variables are given. The outcomes demonstrate the prevalence of  the  clinical  conditions  diagnosed,  inadequate husbandry  and  veterinary  care  accorded  to  owned dogs  in  the  State.  Education  of  dog  owners  on preventive  measures  is  paramount  in  alleviating some of these health problems. http://dx.doi.org/10.5455/javar.2015.b115